Relación entre las Concentraciones de Inmunoglobulina A Salival y Caries en Niños de 6 a 14 años de la Institución Educativa Ana Elisa Cuenca Lara del Municipio de Yaguará (2020)
Introduction: Saliva is considered an important marker that can determine a person's oral health condition; it has multiple functions; one of these is to act as an antimicrobial agent against the pathophysiology of infectious processes such as caries and gingival disease, where microorganisms are one of the most important etiological factors; It is composed of Immunoglobulin A (IgA), which constitutes approximately 15% of serum immunoglobulina and predominates in its secretory form (IgA) in saliva. Objective: the aim to determine the relationships between salivary immunoglobulin A concentrations and dental caries in children from 6 to 14 years of age from the Ana Elisa Cuenca Lara educational institution in the municipality of Yaguará. Materials and Methods: The methodology includes an in-depth, descriptive observational cross-sectional study, from a non-invasive saliva collection using a radial immunodiffusion technique to a sample of 30 children, the results will be processed using descriptive statistics using stata 14 software. Results: The characteristics of the study population show that 81% of children were in an ICDAS range of 1 to 6 with caries, of which 16% have ICDAS type 6, which causes damage to the cavity with extensions of the more than 50% of the dental surface; 17% of this population brushes before each meal, which corresponds to poor hygiene and hygiene practices of the oral system